(untitled) (Journal of Engineering, 2008)
In a typical reservoir a sediment layer of considerable depth may be deposited on the top of exposed bedrock foundation. In this research an analytical solution was proposed to solve the case of the vertical acceleration with infinite reservoir with existence of such sediment layer. The results indicate that as the depth of sediment increases, the pressure increases also. The behavior is found to be affected by the change of the degree of saturation of the sediment layer. As this degree of sediment decreases the developed Hydrodynamic pressure increase. A comparison between the case of stiff and soft foundation indicates that the pressure values are always greater for the stiff foundation.